Organizational Citizenship Behavior and Organizational Performance: A Literature Review - Arquimino Ramos; Lena Ellitan (CV. ULIL ALBAB CORP, 2023)
This paper is to explore the relationship between Organizational Citizenship Behaviour and organizational performance in both private and public organization. OCB has significant impact on organization performance as its shows in several researches and literature review by schoolar. Research in the field of business and management confirms that employees are activators of organizational resources and, therefore, are considered an important asset of the organization. Other available literature confirms the assumption that high employee citizenship behavior is the most influential factor and contributes a lot to the success of company performance. The contribution of fundamentally effective leadership to employee commitment and citizenship cannot be ignored.